COMPREHENSIVE ANALYSIS OF FOREIGN TRADE ACTIVITIES (Web of Teachers: Inderscience Research, 2026)
The article discusses the issues of comprehensive assessment of such foreign trade activities as re-export and re-import, which have been relatively less studied in scholarly research. The role and significance of re-export and re-import in the analysis of foreign trade activities are clarified. The author presents recommendations on the factorial analysis of the share and dynamic changes of re-export, re-import, and other customs regimes in foreign trade. Conclusions regarding the adoption of effective management decisions through the analysis of foreign trade activities based on customs regimes are also provided.